Vertical stratification mediates climate-driven body size shifts in temperate grassland Collembola - Rui Yin; Rui Wu; Iwona Gruss; Paul Kardol; Nico Eisenhauer; Martin Schädler (Applied Soil Ecology, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Metagenomic insights into the influence of rhizosphere microbiome functional profiles for soil phosphorus mobilization under Pseudomonas combinations and phosphate addition - Xiaolei Yang; Qi Li; Changning Li; Xinrui Xu; Yaxuan Liu; Kerui Wu; Tuo Yao (Applied Soil Ecology, 2026)

Soil fungal distribution and environmental drivers in reclaimed salt marshes of the Yangtze River estuary - Hongrui Wu; Qingqiang Chen; Jiazuo Song (Applied Soil Ecology, 2026)

Second-order accurate implicit finite volume method for two-dimensional modeling of PFAS transport in unsaturated porous media with variable surface tension - Rui Wu; Xiaoxing Li; Yuanyuan Sun; Piotr Szymczak; Wentao Jiao (Advances in Water Resources, 2023)